Re-Operations: A Two Year Experience at Gezira National Centre for Pediatric Surgery-Sudan - Idris.A, Abdalla; Nugud, Faisal.A.; Aboaaglla, Omer. A.M. (Gezira Journal of Health Sciences, 2017)
Background: The development of pediatric surgical care in Africa has suffered from the neglecance of health policy makers, yet surgery remains an essential component of basic healthcare and an important means of providing preventive and curative treatment. Although the Sudan started with very few specialists who were trained in pediatric surgery to overcome the need of this specialty which started in the late of 70 th and early of 1980 th with only 5 surgeons.Re-operative surgery in pediatric patients is a challenge that is confronted by every surgeon, a particular operation may be initially done and followed by appropriate post-operative care, functional or anatomical problem may need further surgical intervention. Objective:   To evaluate the magnitude of re-operation in pediatric patients seen at GNCPS. Methods: This is a retrospective and prospective descriptive hospital based study that was conducted over two years as from March 2014 to Feb2016 at GNCPS. The study includes all pediatric surgical patients who needed a redo surgery.  Result: The number of patients studied were111.The age distribution of studied group, the most common age group was less than 5year( n= 78) patients representing 70.3 %, followed by age group 6-10 year (n=19) 17.1% and the last age group 11-15(n=14) 12.6%. The ratio of male to female is 5.16:1. 61.3 %( n=68) of patients from the rural areas while 38.7% (n=32) from urban areas. The person who did the first operation: 47.7% (n=53) were done by pediatric surgeons, 28.8% (n=32) operated by registrars 18% (n=20) done by medical officers, 5.4% (n=6) operated by general surgeons. The final outcome of the patients: 49.5% (n=55) of them were alive without complications 35.1% (n=39) alive with complications, Number of patients who died were 15.3% (n=17). Conclusion: The majority of redo-operations are done under the age of 5year. Less than 50% of the initial operations were done by specialized pediatric surgeons reflecting the gross shortage of surgeons in this discipline. More than 80% of initial operations were done at specialized centers reflecting the poor set-up at the center. The gastrointestinal (GIT) system was associated with the most surgical redo. The mortality following redo-operations was high.